Adding LCMPT Terms to Local Catalog Records for Notated Music for Voice and Piano. (2nd January 2022) - Scott, Amanda L.
ABSTRACT: Medium of performance is a valuable way to find music materials, but it is challenging to search by medium in library catalogs. Songs for specific voice types are especially difficult to look for using legacy metadata such as subject headings. This article describes a project to add terms from Library of Congress Medium of Performance Thesaurus for Music to records for scores for songs with piano in an academic library catalog. Appropriate terms are identified by examining subject headings and uncontrolled fields in the records. Adding these terms can enhance discovery and enables deeper analysis of the collection.